A notable impact of lipid matrices on cholesterol bioaccessibility from phytosterols-loaded nanostructured lipid carriers during in vitro intestinal digestion. (April 2023) - Guo, Shujing; Ma, Chuanguo; Hu, Yuyuan; Song, Zhenjia; Wang, Tong; Yang, Ruinan
Abstract: Encapsulation of phytosterols in nanostructured lipid carriers (NLCs) is an effective approach to improve their physicochemical properties, but the interaction of phytosterols in NLCs with cholesterol can be affected by lipid matrices. The objective of this study was to screen a desired phytosterols-loaded NLC (PS-NLC) formulation to reduce the absorption of intestinal cholesterol. A series of formulations were prepared using amphipathic glycerol monostearate (GMS) as the solid lipid fraction to increase lipid compatibity with phytosterols. All formulations showed a lowering effect on cholesterol bioaccessibility through in vitro intestinal digestion. And the PS-NLCs with medium chain triglycerides (MCT) as the liquid lipid showed significantly higher inhibition of cholesterol bioaccessibility (accessible fraction for intestinal absorption) than the formulations with long chain triglycerides (LCT), which could due to the solubilization of cholesterol by hydrolysis products of LCT, suggesting a notable impact of lipid type on cholesterol bioaccessibility. Furthermore, the analysis of distribution of phytosterols and cholesterol revealed a cocrystallization mechanism occurred during in vitro digestion. This study provides a certain reference for designing phytosterol-ingredient agents with a better hypocholesterolemic effect in water-dispersible functional foods. Graphical abstract: In this study, we investigated the embedding of phytosterols by different nanostructured lipid carriers formulations, and the fate of these formulations in in vitro intestinal digestion. The results showed a notable impact of lipid matrices on cholesterol bioaccessibility as nanocarriers with medium chain triglycerides as the liquid lipid component led to a significantly lower cholesterol bioaccessibility than with long chain triglycerides. Image 1 Highlights: Phytosterols loading in NLCs achieved their enrichment in water-dispersible foods. Phytosterols loaded NLCs lowered cholesterol bioaccessibility during digestion. MCT systems showed a higher micellar cholesterol inhibition effect than LCT systems. Cocrystallization of phytosterols and cholesterol might be the mechanism of action.